Microstructural study on the grain growth inhibition of VC-doped WC-Co cemented carbides. (January 2017) - Okada, K.; Osada, A.
Abstract: Recent works investigating the grain growth inhibition mechanism by rapidly quenched VC-doped cemented carbides are reviewed. The rapid quenching enables to observe microscopic features at the sintering state of cemented carbide. The formation of (W, V)Cx layers at WC/Co interfaces has already occurred during liquid phase sintering which control the grain growth rate. The structure and thickness of (W, V)Cx layers are related to the lattice coherency between (W, V)Cx and WC grains. The difference in the interface structure with different carbon content results in the difference of grain growth rate. Highlights: The rapid quenching of VC-doped cemented carbides enables to observe microscopic features at the sintering state. The formation of (W, V)Cx layers at WC/Co interfaces has already occurred during liquid phase sintering which control the grain growth rate. The structure and thickness of (W, V)Cx layers are related to the lattice coherency between (W, V)Cx and WC grains. The difference in the interface structure with different carbon content results in the difference of grain growth rate.